2020
DOI: 10.3389/fphys.2020.00532
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta and Sonic Hedgehog Signaling in Palatal Epithelium Regulate Tenascin-C Expression in Palatal Mesenchyme During Soft Palate Development

Abstract: TGF-β Regulates TNC During Palatogenesis signal cascade may work in the later stage of palatogenesis when cranial neural crest cells have differentiated into fibroblast-like cells. The spatiotemporal regulation of ECM-related proteins by TGF-β and SHH signaling may contribute not only to tissue construction but also to cell differentiation or determination along the anterior-posterior axis of the palatal shelves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…This is consistent with previous studies which have shown that ethanol can affect TGFβ signalling in the brain [6568] and the articular cartilage [69]. Defects in cleft palate formation are evident in FASD models and this process requires crosstalk between the TGFβ pathway and Sonic hedgehog (Shh) [70, 71]. Interestingly, the detrimental effects of PAE can be partially remedied by increased Shh [31], adding further evidence that these may be key pathways in the underlying pathology of FASD.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which have shown that ethanol can affect TGFβ signalling in the brain [6568] and the articular cartilage [69]. Defects in cleft palate formation are evident in FASD models and this process requires crosstalk between the TGFβ pathway and Sonic hedgehog (Shh) [70, 71]. Interestingly, the detrimental effects of PAE can be partially remedied by increased Shh [31], adding further evidence that these may be key pathways in the underlying pathology of FASD.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, Noggin was reported to induce Scx transcription during the early specification of limb tendons (Schweitzer et al, 2001), while in this study, the overexpressed Noggin inhibited the tenogenesis. The contradictory phenomena may result from the signaling other than BMP-Smad signaling, which was altered by the overexpressed Noggin (Ohki et al, 2020). Actually, the decreased Scx transcription in both the Osr2-cre KI ;pMes-Noggin and Myf5cre;pMes-Noggin soft palates was supposed to be regarded as a sign of the impaired tenogenic differentiation and maturation, because Scx was also essential for the maintenance of tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Sonic hedgehog signaling is essential for orofacial development and mediates epithelialmesenchymal interactions that control palatal outgrowth [10]. A recent study revealed that TGFβ and SHH together regulate the expression of tenascin-C in developing soft palates [140]. Tenascin-C is a glycoprotein of the extracellular matrix, and its expression overlays the migratory routes of cranial neural crest cells while forming future palate [141].…”
Section: Sonic Hedgehog Signalingmentioning
confidence: 99%